The post-birthday world - Shriver, Lionel (London : HarperCollins Publishers, 2007)
A tale told from the parallel perspectives of two possible timelines considers the life of American expatriate Irina McGovern, who in one reality stays faithful to her disciplined American intellectual partner, and in the other runs off with an exuberant British friend.
Keywords: Women illustrators -- Fiction; Snooker players -- Fiction; Americans -- England -- London -- Fiction; Mate selection -- Fiction; Married people -- Fiction; Domestic fiction